The Nano-Magnetic Dancing of Bacteria Hand-in-Hand with Oxygen - Talib,Ayesha (2017)
ABSTRACT Magnetotactic bacteria are mostly microaerophilic found at the interface between oxic-anoxic zones. We report a magnetotactic bacterial strain isolated from an oil refinery sludge sample that grows aerobically in simple chemical growth medium, 9K. They open a new window of isolation of magnetic nanoparticles through an easy natural living system.